Novel integration between propane pre-cooled mixed refrigerant LNG process and concentrated solar power system based on supercritical CO2 power cycle - Ahmad K. Sleiti (14778229) (2023)
Liquefaction of natural gas (LNG) is an energy-intensive process with large CO2 emissions. This study addresses these problems by introducing a novel hybrid integration between the propane pre-cooled mixed-refrigerant (C3MR) liquefaction process and concentrated solar power (CSP), utilizing an intercooled supercritical CO2 power block. The proposed system is designed to minimize or eliminate the need for thermal energy storage (TES) and reduce CO2 emissions while providing economic benefits. These benefits are obtained mainly by recovering the cold energy of the flash-gas of the C3MR process through the precooling process of the sCO2 cycle. Then, the flash-gas is stored and combusted (using an auxiliary heater (AH)) at nighttime or when CSP is insufficient to meet the power demand. Five integration cases are evaluated from energetic, exergetic, economic, and environmental points of view: the sCO2 cycle is driven by CSP and its thermal energy storage (TES) without AH in Case-1, by CSP+TES+AH in Case-2 to Case-4 with different contribution from TES and AH, and by CSP+AH without TES in Case-5. In addition, this study optimizes the operating parameters of the hybrid system to further enhance its economic and environmental benefits. The proposed system reduces the CSP field size, minimizes or eliminates the need for TES, and reduces or eliminates CO2 emissions. The optimized results show that Case-2 and Case-5 reduced the levelized cost of electricity from 14.16¢/kWh to 10.35¢/kWh and 8.19¢/kWh, respectively, and reduced the CO2 emissions by 86% and 36%. This study contributes to the field by introducing a novel hybrid integration between the C3MR process and CSP system, providing thorough evaluations of its performance and benefits, and providing significant benefits to the decarbonization strategies of LNG and other industrial processes. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2023.04.012